Policy coherence : vital for global development (OECD Pub. ParisFR, 2003)
Defines policy coherence for development and indicates why it is important, yet difficult to achieve. Notes how developed countries benefit and the key areas for making progress. Identifies the role of the OECD.
Bibliography: p. 8